Risk perception, burnout, and knowledge of chemotherapy nurses during the COVID-19 pandemic - Lokman Koral (SERNEV, 2021)
Introduction: Not every individual exposed to the same stressors will develop the same symptoms of burnout. We aimed to evaluate the risk perception and burnout of chemotherapy nurses working with patients having possibly low immune resistances and investigate the relationship with the COVID-19 knowledge of the participants.Methods: We carried out a cross-sectional study in oncology nurses between May and June 2020. Using Delphi panels, instruments were developed on COVID-19-related burnout and risk perception. Of the 857 nurses registered to the Association of Oncology Nurses, 267 responded to an online survey, including 28 items on demographic features, burnout, risk perception, and COVID-19 knowledge.Results: The mean age of the participants was 34.8±8.4 (min. 20, max. 58) years. The mean risk perception scores were 17.34±3.00 (min. 6, max. 24) and burnout scores were 16.74±4.44 (min. 2, max. 27), both above two-thirds of the maximum possible limits. Knowledge scores, on the other hand, were relatively high (72.09±20.0%). COVID-19 knowledge scores showed a significant positive correlation with burnout scores (r=0.499, p lt;0.001) but a negative correlation with age (r=-0.153, p=0.013). There was no significant correlation between burnout scores and risk perception or risk perception and age (p gt;0.05). Linear regression analysis showed that after adjusting for the possible confounders, the COVID-19 knowledge score was the only significant variable independently affecting burnout scores (Beta=0.109, 95% Confidence Interval (CI): 0.086-0.133, p lt;0.001).Conclusions: During the COVID-19 pandemic, chemotherapy nurses are under significant pressure concerning risk perception and burnout. Increasing the knowledge of the nurses by in-service training could raise their awareness and risk perception. However, precautions must be taken to prevent work-related exhaustion and support nurses experiencing burnout.